The Relationship Between Elements of Gender Injustice and Divorce in Makassar City's Religious Courts (Data from 2017 To September 2021) - Arfan M; Mansur Radjab; Mardiana E Fachri (Journal of Public Administration and Government, 2022)
The purpose of this study is to gather background information on the growing number of divorce cases in the Religious Courts Class IA Makassar and to examine the causative elements that arise from the divorce case. The researchers employed a qualitative technique to accomplish this purpose. This study is place in Makassar's Religious Courts Class I.A (first level). Primary data sources (key informants) and secondary data sources (official documents such as case reports and/or divorce case files from 2017 to September 2021) were used in this study. In this study, data was gathered through interviews with Makassar Religious Court Judges and documents. The descriptive qualitative data analysis approach is used, and the resulting data is then processed using descriptive analysis. According to the study's findings, the Religious Courts classify the causes for divorce as follows: 1) Zina, 2) Drunk, 3) Madd 4), gambling, 5), abandoning one of the parties, 6) Sentenced to incarceration, 7) Polygamy, 8) Domestic Violence, 9) Body Disability, 10) Constant Discord, 11) Forcible Marriage, 12) Apostate, and 13) Economy.